High-resolution carbon dioxide concentration record 650,000–800,000 years before present - Lüthi, Dieter; Le Floch, Martine; Bereiter, Bernhard; Blunier, Thomas; Barnola, Jean-Marc; Siegenthaler, Urs; Raynaud, Dominique; Jouzel, Jean; Fischer, Hubertus; Kawamura, Kenji; Stocker, Thomas F. (Nature, 2008)
International audience Changes in past atmospheric carbon dioxide concentrations can be determined by measuring the composition of air trapped in ice cores from Antarctica. So far, the Antarctic Vostok and EPICA Dome C ice cores have provided a composite record of atmospheric carbon dioxide levels over the past 650,000 years. Here we present results of the lowest 200 m of the Dome C ice core, extending the record of atmospheric carbon dioxide concentration by two complete glacial cycles to 800,000 yr before present. From previously published data and the present work, we find that atmospheric carbon dioxide is strongly correlated with Antarctic temperature throughout eight glacial cycles but with significantly lower concentrations between 650,000 and 750,000 yr before present. Carbon dioxide levels are below 180 parts per million by volume (p.p.m.v.) for a period of 3,000 yr during Marine Isotope Stage 16, possibly reflecting more pronounced oceanic carbon storage. We report the lowest carbon dioxide concentration measured in an ice core, which extends the pre-industrial range of carbon dioxide concentrations during the late Quaternary by about 10 p.p.m.v. to 172–300 p.p.m.v.